CULTURAL SIGNS IN TEXTS OF LATGALIAN BANDS - Gusāns, Ingars (Via Latgalica, 2017)
During ten years, since Latgalian popular music has returned to the mainstream Latvian music stage, 44 Latgalian music albums have been released. The lyrics of these songs are written by musicians, Latgalian and Latvian poets and as a result of teamwork of poets and music authors. The subject of the present research is represented by cultural signs in the song texts of Latgalian bands; the research object is song lyrics of Latgalian bands. Sources selected for the research are the song texts of Latgalian bands and performers: "Borowa MC", "Bez PVN", "Dabasu Durovys", "Green Novice", Laura Bicāne, "Kapļi". Some musicians and bands use Latvian and Latgalian folk songs in their music, yet they are not discussed in the present research. Other musicians use works of Latgalian poets, which are mentioned here only for comparison. Therefore, the key focus is on texts written by musicians themselves, collected from the released music album brochures and from correspondence with band members. The texts of schlager music bands are not examined here either, as they are worth making a separate research.It must be admitted that cultural signs in the examined texts do not occur particularly often, although the feature of the post-modernist culture is related to reassessment and mock of previous culture, the song lyrics are still rather romantic, traditional and compliant with the requirements of mass culture. The use of cultural signs is not characteristic of bands "Green Novice", "Bez PVN" and performer Laura Bicāne, therefore, the song texts of bands "Borowa MC", "Dabasu Durovys" and "Kapļi" are analysed the most. The research has been carried out based on the method of structural semiotics (J. Lotmans, R. Veidemane) by analysing cultural signs found in the selected texts.The signs related to cultural history are rather traditional: Latgale, Latgalians, rarely, some specific natural or geographical objects relevant to cultural historical events or associated exactly with the Latgale region. However, the search for territorial and ethnic identity and its construction for oneself and others (mostly, neighbours of other regions) is one of the main questions in the lyrics. As the mentioned bands "Borowa Mc", "Dabasu Durovys" and "Bez PVN" play popular, mass-oriented music, their texts are mostly intended for broad public, therefore, the first features that characterize the song lyrics of Latgalian bands are the cultivation and preservation of stereotypes. These stereotypes are divided into two groups:1) favourable, emotionally uplifting, sometimes even rousing self-confidence; 2) critical, prejudiced, causing negative atmosphere and emotions.The poetical rock band "Kapļi", which belongs to an alternative direction of Latgalian music and has ironic, sarcastic texts, sing about cultural signs related to Latgale in a completely different way. Their lyrics show a different view of things that are holy, inviolable, and indisputable to many Latgalians.Regarding cultural signs representing the folkloristic level, it must be noted that in this research ‘folkloristic’ is meant in the broadest sense of this word (not only folk compositions, but also events, objects, things that have become a part of folklore over time, often becoming subjects of literary tales), for instance, Pinocchio, the main character combines several characters: a fool, a body-builder, and even a lyrical ego seeking for its own identity. All character appearances, which are reflected in other songs about the modern hero, suggest that the character avoids activity or makes the new world unstable by drawing, making it from plasticine, using the phone, and consequently, creates a virtual world which is modern and transitory. "Dabasu Durovys" reveals their life philosophy and search for meaning with the help of historical cultural signs, for instance, the river Rubicon, known from ancient times, meaning the breaking of links to the past and not returning to previous situation, or the royal court of the Sun King, that symbolizes absolute monarchy, or Napoleon, etc.“Little man” and his daily life are related to another group of cultural signs. Depiction of daily life in poetry shows on the one hand that the author values the place and time of his life; on the other hand it demonstrates an artistic approach to everyday reality. These texts usually convey tragically ironical feeling and show modern typical dramas right beside us. Such characters most frequently appear in the texts of the bands "Kapļi" and "Dabasu Durovys".Even though cultural signs do not appear in the texts of Latgalian bands frequently, they are diverse. Cultural historical signs, which appear in patriotic and ironic lyrics, reveal authors’ homeland Latgale and Latgalians with their typical positive and negative stereotypes. Cultural signs related to Latvia and Europe highlight ironically sharp reality of emigration and infrequent visits to Latvia and are bound to several historical periods, which are mostly related to domestic, rarely social political situations.